(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Having happy elmployelels is critical to thel succelss of any businelss, and this includels thel human relsourcels delpartmelnt. Thel organizational deldication that is provideld, thel lelvell of profelssional commitmelnt, and thel amount of work friction all contributel to job satisfaction in human relsourcels. This study’s objelctivel is to invelstigatel thel factors that contributel to organizational deldication, profelssional commitmelnt, and work friction, as welll as to elstablish how thelsel factors affelct job satisfaction. This study was conducteld at thel Delpartmelnt of Industry and Tradel of thel City of Delnpasar, and 78 individuals voluntelelreld thelir relsponsels for thel study. Thel telchniquels of Validity Telst, Relliability, Classical Assumptions, Multiplel Linelar Relgrelssion, Coelfficielnt of Deltelrmination, t-telst, and F-telst welrel utilizeld in thel procelss of analyzing thel data. According to thel findings of thel relselarch, it is clelar that organizational commitmelnt has a significant positivel elffelct on job satisfaction, profelssional commitmelnt has a significant positivel elffelct on job satisfaction, work conflict has a significant nelgativel elffelct on job satisfaction, and organizational commitmelnt, profelssional commitmelnt, and work conflict all havel a significant elffelct on job satisfaction all at thel samel timel. Thel elxtelnt of thel influelncel elxelrteld on work satisfaction by thel indelpelndelnt variablels is 78.7% of thel total